2015
DOI: 10.1002/hpm.2289
|View full text |Cite
|
Sign up to set email alerts
|

How to attract health students to remote areas in Indonesia: a discrete choice experiment

Abstract: This study confirmed the importance of combination interventions in attracting and retaining health workers in remote areas of Indonesia. Money is not the only factor affecting student preferences to take up a rural post; good management and better facilities were viewed as important by all health students. Addressing health student preferences, which are the candidate of future health workforce, would help the nation solve the recruitment and retention issues. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 25 publications
9
52
1
2
Order By: Relevance
“…Final year health students viewed a higher salary as a very important attribute. This reinforces previous studies in China [33], which might be due to the fact that they are less satisfied with their salaries. As Chinese health students still value the most fundamental needs, the lowest level of needs in Maslow's theory, that is basic needs for safety [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Final year health students viewed a higher salary as a very important attribute. This reinforces previous studies in China [33], which might be due to the fact that they are less satisfied with their salaries. As Chinese health students still value the most fundamental needs, the lowest level of needs in Maslow's theory, that is basic needs for safety [21].…”
Section: Discussionsupporting
confidence: 91%
“…Unlike several studies showing that financial incentives were not found to be most powerful policy levers [13,26,28,31,33,36,38,44]. However, our findings conformed that monthly income had a significant impact on the job choices of undergraduate health students, similar with other studies [10,37,45].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Apesar de esse atributo se mostrar relevante em diversos experimentos de preferência declarada 16,19,20 , no presente estudo sua importância se mostrou ainda maior, o que também foi encontrado em experimentos com estudantes realizados em Gana 20 e na Indonésia 36 . Isso pode ser atribuído à falta de vivência, por parte dos estudantes, da realidade do trabalho como médicos, em que outros atributos passam a ser mais valorizados.…”
Section: Discussão E Conclusãounclassified